Mental Health Screening in North Sulawesi, Indonesia: Kessler 6 pilot data and needs assessment results from the LearnToLive Indonesian Health Initiative. (22nd September 2015) - Kinzie, Erik; Blake, Adam; Alvares, Ryan; McCormick‐Ricket, Iben
Abstract: Introduction: Communities around the world are increasing their focus on mental health and substance use disorders. However, the struggle to identify and treat patients remains great. The sequelae of these disorders, including severe chronic disability and suicide, are significant, and its impact is felt most in lower and middle‐income countries. In the rural and underserved region of North Sulawesi, Indonesia, there are limited data published regarding the prevalence of depression, anxiety, and other symptoms of psychological distress. Methods: In order to characterize and quantify some specific areas of psychological distress, the LearnToLive Indonesian Health Initiative completed a retroactive review of Kessler 6 data from 697 people in rural communities of North Sulawesi. Results: Our results demonstrate a rate of near 10% for psychological distress, particularly with anxiety and depressive symptoms. We also found that the village of Sapa scored higher on most of the subcomponents of the screen compared with the other villages in the study. Discussion: While the Kessler 6 screening tool is not diagnostic, our results suggest significant mental health issues in need of further exploration and research. We found that these results exist in an environment with high stigma, limited education regarding mental illness, and limited outpatient services. The results from this analysis will hopefully guide future mental health education in the region and will ultimately assist in the development of the clinical infrastructure needed to effectively identify, treat, and manage mental health conditions.